1-Hydroxy-2-methyl-2-propyl Isocyanide (HMPI) as a New Convertible Isocyanide for the Ugi Four-Component-Coupling Reaction - Oikawa, Masato; Sugamata, Yutaro; Chiba, Manami; Fukushima, Koichi; Ishikawa, Yuichi (Synlett, 2013)
The Ugi reaction is a useful four-component coupling reaction for α-(acylamino)amide. However, selective transformation of the two amides is generally difficult. Here, we report 1-hydroxy-2-methyl-2-propyl isocyanide (HMPI) as a new member of a ‘convertible isocyanide’ class used to solve the problem. HMPI is odorless and shows good reactivity in the Ugi reaction to give N-(1-hydroxy-2-methyl-2-propyl) amides, which are smoothly converted into esters upon Zn(OTf)2-mediated solvolysis. Overall, structurally diverse α-amino acid esters are readily accessible in two steps by using HMPI.
Keywords: amides; chemoselectivity; multicomponent reactions; zinc; esters